Rozważania o procesie poszukiwania tematu - Pabich, Marek (Wydawnictwo Politechniki Łódzkiej, 2021)
Autor dzieli się z czytelnikiem przemyśleniami na temat procesu poszukiwania tematu wystąpienia, który ma zostać zaprezentowany w trakcie 12. Ogólnopolskiego Seminarium Naukowego Studentów Architektury oraz ukazać się drukiem w wydawnictwie pokonferencyjnym. Obszar poszukiwań sprowadza się do szeroko pojętych pojęć podróży i doświadczenia, co wiąże się z wiodącymi zagadnieniami podejmowanymi w trakcie Seminarium.

The author shares with the reader his thoughts on the process of searching for the topic of the speech to be presented at the 12th National Scientific Seminar of Architecture Students and to be published in the post-conference publication. The search area is reduced to the broadly understood notions of travel and experience, which is related to the leading issues raised during the Seminar.
Considerations on the topic search process
Keywords: podróż; doświadczenie; architektura; travel; experience; architecture